Spatiotemporal and species variations in prokaryotic communities associated with sediments from surface-flow constructed wetlands for treating swine wastewater. (October 2017) - Jia, Fen; Lai, Cui; Chen, Liang; Zeng, Guangming; Huang, Danlian; Liu, Feng; Li, Xi; Luo, Pei; Wu, Jinshui; Qin, Lei; Zhang, Chen; Cheng, Min; et al.
Abstract: Microorganisms are the main mechanisms of pollutants removals in constructed wetlands (CWs) used for wastewater treatment. However, the different biological processes and variations of prokaryotic community in CWs remain poorly understood. In this study, we applied a high-throughput sequencing technique to investigate the prokaryotic communities associated with sediments from pilot-scale surface-flow constructed wetlands (SFCWs) treating swine wastewater (SW) of varying strengths. Our results revealed that highly diverse prokaryotic communities were present in the SFCWs, with Proteobacteria (16.44–44.44%), Acidobacteria (3.25–24.40%), and Chloroflexi (5.77–14.43%) being the major phyla, and Nitrospira (4.14–12.02%), the most dominant genus. The prokaryotic communities in the sediments varied greatly with location and season, which markedly altered the microenvironmental conditions. Principal co-ordinates analysis indicated that SW strength significantly influenced the community structure in sediments of the SFCWs, and canonical correspondence analysis illustrated that the shifts in prokaryotic communities were strongly related to NO3 − –N and TN in winter; and in summer with NH4 + N, NO3 − –N, NO2 − –N, TN, TP, SOM, and pH. In conclusion, the use of high-throughput sequencing greatly enhanced our understanding of prokaryotic communities with different functional groups in SFCWs. Graphical abstract: Highlights: Three-stage surface-flow constructed wetlands (SFCWs) treatment was effectively. Proteobacteria dominated sediments from SFCWs for treating swine wastewater. Prokaryotic communities in sediments varied greatly with location and season. Swine wastewater strength markedly influenced community structure in sediments.